Norway in the First World War - Knutsen, Jan Normann (Folia Scandinavica Posnaniensia, 2007)
The article describes the economic, social and political consequences of World War I for Norway. It deals with how the country’s chosen neutral stance was being undermined and in this context its relationship with the belligerent parties. It tries to answer the question why Norway did not become directly engaged in the war, and finally looks into the changes in Norwegian society and foreign policy brought about by the war.